Traditional livestock breeding practices of men and women Somali pastoralists: trait preferences and selection of breeding animals - Marshall, Karen; Mtimet, Nadhem; Wanyoike, Francis N.; Ndiwa, Nicholas N.; Ghebremariam, H.; Mugunieri, Lawrence Godiah; Costagli, Riccardo (Wiley, 2016)
Somalia, one of the world's poorest countries, has livestock as the mainstay of the economy, with an estimated 65% of the population engaged in the livestock sector. This paper presents a gendered study on the traditional livestock breeding practices of Somali pastoralists for camels, cattle, sheep and goats, with a focus on documenting livestock traits of importance, the criteria used to select male breeding animals and the criteria used to cull female breeding animals. Data for the study were obtained by performing participatory rural appraisals (PRAs) with separate male and female pastoral groups from 20 settlements of the Tog-Dheer region of Somaliland (in north-western Somalia). In total, more than 500 pastoralists were involved. In terms of livestock ownership, goats were the most common species kept (97% of all households), followed by sheep (64%), camels (37%) and cattle (9%), with considerable herd size variation across households. Traits of key importance to the pastoralists varied by species and gender of the PRA group, but included adaptedness to harsh environmental conditions, high market value/high meat production and high milk production. The pastoralists practised sensible criteria for the selection of male breeding animals for all species, capturing aspects of productivity (milk yield, reproduction), adaptedness (good hardiness) and marketability (body size and conformation). Similarly, they practised sensible criteria for culling of female breeding animals, with females removed from the herd primarily for poor performance, but also to meet the livelihood needs of the family. Differences in the selection and culling criteria were noted by species, as well as gender of the pastoralists. On the whole, there was strong alignment between the livestock selection criteria used by the Somali pastoralists, their reasons for keeping livestock and the market requirements. This is not surprising given the intimate and long-standing relationship between Somali pastoralists and their livestock.